Efforts to Improve Young Generation Problem Solving in the Era of Globalization Using Six Thinking Hats Analyzed with SPSS: Solving Literacy, Read, and Hoax - Theron, Jurgen; Richardo, Enrico; Sutedjo, Marco; Syarifudin, Muh. (Bumi Publikasi Nusantara, 2024)
Today's Young Generation is often confused by the choices they have to make to enter college. With so many choices available, it can affect the choice of young people in making decisions to take the majors and campuses of their choice, as a result, many young people choose the wrong majors and end up unused by individuals, which wastes time and effort. As many as 87% of RI students feel they have the wrong major because many of them choose to follow their friends' and parents' reasons. Since many young people have this problem, the author researched to help young people in this position to think more effectively and make better decisions, namely with six thinking hats.